Histomorphological Patterns of Focal Segmental Glomerulosclerosis and Their Clinical Correlation in Tertiary Care Hospitals in Bangladesh (Sir Salimullah Medical College Journal, 2023)
Background: Being one of the commonest glomerular diseases in adults and a major etiology of the nephrotic syndrome, Focal Segmental Glomerulosclerosis (FSGS) gradually progresses towards end-stage renal disease (ESRD). According to pathogenesis, FSGS can be classified into primary or secondary ones and in both instances, histomorphological findings are nearly indistinguishable. Five histomorphological variants of primary as well as secondary focal segmental sclerosis have already been accepted, for instance, NOS (not otherwise specified), tip, cellular, perihilar, and collapsing variants. Nonetheless, primary FSGS is a diagnosis of exclusion and all the time, primary and secondary FSGS can not be distinguished discernibly. For this reason, correlation with clinical and biochemical parameters are extremely important. The present study was undertaken to identify various histomorphological patterns of FSGS by light microscopy and immunofluorescence study at tertiary care hospitals in Bangladesh as well as to correlate those patterns with clinical, biochemical parameters and additional histologic findings.Methods: This is an observational & cross sectional study which was conducted among 57 paraffin blocks of renal biopsy specimens of histologically confirmed FSGS cases including all age groups and both sexes, which were collected from department of Pathology, BSMMU & Kidney foundation hospital & research institute, Mirpur, Dhaka. Renal biopsies received for light microscopy only and biopsies that contained less than eight glomeruli were exluded from the study . Routine Haematoxylin & Eosin (H&E), Periodic Acid Schiff (PAS), Jones silver & Masson’s trichrome stains were used to evaluate renal biopsy specimens & histomorphological patterns of FSGS were identified. Data regarding clinical & biochemical parameters were collected from patient’s medical records. Statistical analyses were performed by SPSS-22.Result: In our study, it was observed that, among 57 biopsies, 35(61.4%) biopsies were diagnosed as NOS, 12(21.1%) biopsies as perihilar, 4(7.0%) biopsies as tip, 3(5.3%) biopsies as collapsing and 3(5.3%) biopsies as cellular variant. No clinical and biochemical parameters were significantly associated with these histomorphological patterns of FSGS. Regarding additional histologic features, thick walled blood vessels was significantly associated with histomorphological patterns.Conclusion: This study was conducted on only two tertiary level hospitals in Bangladesh, therefore, the result may not reflect the exact scenario of Bangladesh. It is the need of the moment to mention the histomorphological patterns of FSGS in renal histopathology reports. Moreover, logistic support is a necessity to institute nephro-pathology section in the pathology department of all the tertiary care hospitals in order to identify renal glomerular disease precisely. Sir Salimullah Med Coll J 2023; 31: 26-33